Skyrme-Extended-Thomas-Fermi Approach Method In Investigation of Nuclear Ground State Properties of 208Pb - Yacobus Yulianto; Zaki Su'ud (Indonesian Journal of Physics, 2016)
In this research, it is performed the nuclear ground state properties investigation of 208Pb by using the SETF method with SLy4 set parameters. The energy optimization calculation is performed using SETFA code. The SETFA results are in good agreement with the related experiment results, and also with the results of the HFBRAD and HFODD- HFBTHO codes. It is can be indicated that Skyrme-Extended-Thomas-Fermi method can be used to explain the nuclear ground state properties, especially even-stable nucleus.